CD28 costimulatory signal induces protein arginine methylation in T cells. - Blanchet, F; Cardona, A; Letimier, F; Hershfield, MS; Acuto, O (2005)
Protein phosphorylation initiates signal transduction that triggers lymphocyte activation. However, other posttranslational modifications may contribute to this process. Here, we show that CD28 engagement induced protein arginine methyltransferase activity and methylation on arginine of several proteins, including Vav1. Methylation of Vav1 and IL-2 production were reduced by inhibiting S-adenosyl-L-homocysteine hydrolase, an enzyme that regulates cellular transmethylation. Methylated Vav1 was induced in human and mouse T cells and selectively localized in the nucleus, which suggested that this form marks a nuclear function of Vav1. Our findings uncover a signaling pathway that is controlled by CD28 that is likely to be important for T cell activation.